Fabrication and Characterization of Asbestos Free Brake Pads Composite using Elaeocarpus Ganitrus as Reinforcement - Mohamad Afiefudin; Rahmat Doni Widodo; Rusiyanto Rusiyanto (Universitas Muhammadiyah Magelang, 2023)
To minimize potential health hazards, there is awareness to avoid asbestos fibers in brake pads. Therefore, this study aims to produce composite brake pads using Elaeocarpus ganitrus seed powder as a substitute for asbestos. The composition of Elaeocarpus ganitrus seed powder was varied from 8%, 10%, and 12% by weight. The properties of the brake pads, including their morphology, physical characteristics, mechanical performance, and wear behavior, were thoroughly investigated and analyzed. The experimental results showed a positive correlation between the addition of 12% by weight of Elaeocarpus ganitrus and the increase in the density and hardness of the resulting sample. In addition, wear resistance increases with increasing percentage of Elaeocarpus ganitrus. Samples containing 12% by weight of Elaeocarpus ganitrus seed powder gave better properties compared to other composite samples. The research findings indicate that Elaeocarpus ganitrus particles can be an alternative to asbestos in the manufacture of brake pads.